Digital Governance and Public Policy: Legal Challenges and Opportunities in the Era of Artificial Intelligence - Marseliani, Tiara; Marsela B, Tiara (LEX et ORDO Jurnal Hukum dan Kebijakan, 2023)
The rapid advancement of artificial intelligence (AI) presents both opportunities and challenges for public policy and legal systems worldwide. On one hand, AI has the potential to enhance efficiency in public administration, strengthen decision-making processes, and improve access to justice. On the other hand, it raises concerns related to data privacy, algorithmic bias, accountability, and regulatory gaps. This paper explores the evolving relationship between digital governance and public policy, emphasizing the need for adaptive legal frameworks that balance innovation with the protection of fundamental rights. Through a comparative analysis of regulatory approaches in various jurisdictions, the study highlights best practices and proposes recommendations for policymakers to ensure responsible and ethical AI deployment in the public sector.